Solve the following logarithmic equation:

log_{2}(x − 2) + log_{2}(x + 1) = 2

### Want to see the full answer?

Check out a sample Q&A here*star_border*

## Related Algebra Q&A

Find answers to questions asked by students like you.

Q: Solve the following logarithmic equation. log(2x - 2)= log(x + 1) + log(4)

A: Given: log2x-2=logx+1+log4 Now by using the logarithmic property, loga+logb=loga·b…

Q: Solve the following log equation exactly loga(x)=loga(x2-30)

A: This question is based on properties of Logarithm.

Q: Solve the following logarithmic equations. log(3x – 2) = 2 b. log3(x + 25) - log3 (x- 1) = 3

A: To solve the given logarithmic equations, we use some basic logarithmic formulas. Common logarithm…

Q: solve the following logarthemic equation. log4(x+74) + log4(x+11)=3

A: Given, log4x+74+log4x+11=3

Q: Solve the following equation: log3 (x + 16) – log3 x = 2

A: Click to see the answer

Q: Solve the Logarithmic Equation 5 log, x = 4 by following the steps below.

A: Give logarithmic equation : 5 log2x=4

Q: Solve the logarithmic equation: log, (x + 1) + log, (x – 1) = 2. Round to the nearest tenth if…

A: Given logarithmic equation is log5x+1+log5x-1=2

Q: Solve the following equation. log(x-3)-log(x+3)=10

A: Click to see the answer

Q: Solve the following logarithmic equation. log(r - 10) = log(20) %3D log, (10)

A: Click to see the answer

Q: Solve the logarithmic equation: logx + log(x+15) = 2

A: Given information:The given equation is,

Q: solve the following equation. log2(5Vx – 5) + log2(Vx – 1) = 3

A: Given that: log2(5x-5)+log2(x-1)=3

Q: Solve the following equation. log8 x = 1/3

A: We firts use the exponential form of log.

Q: Solve the following logarithmic equation. log x+ log (x +9) = 1

A: Introduction: Scientists immediately adopted logarithms because of a spread of advantageous…

Q: solve the following equation, log2(5vx – 5) + log2(Vã – 1) = 3 |

A: We have to find the value of x

Q: Solve the following equation. log10 x = 3

A: Click to see the answer

Q: Solve the logarithmic equation for the unknown x. 2 log4 x = 1

A: Click to see the answer

Q: Solve the following logarithmic equation: K•3 B-5 log2(x – K – B – 3) = log2 (x + K + B – 12) %3D

A: Click to see the answer

Q: Solve the following logarithmic equation: log x + log(x − 1) = log(4x)

A: Simplify logarithmic equation

Q: Solve the following equation: log 3 x + log 3 ( x - 6 ) = 3

A: Given: log3x+log3x-6=3 for solving this equation first we find domain of given equation we know that…

Q: Solve the following logarithmic equation. log 3(x+ 10) + log 3 (x+ 18)= 2

A: Click to see the answer

Q: solve the following equation log2 (5Vx – 5) + log2(v – 1) = 3

A: Click to see the answer

Q: Solve the equation log(x+2)+log(x-1)=1

A: The given equation is log(x+2)+log(x-1)=1

Q: Solve the equation log(x+2)+log(x-1)=1

A: Given Data: Equation: log(x+2)+log(x-1)=1 The porduct rule of logerithmic is, loga+logb=logab…

Q: Solve the logarithmic equation for the unknown x. log(x – 5) = 3 X = 6

A: Click to see the answer

Q: Solve the logarithmic equation. Be su log x+ log s(7x- 1) = 1

A: Click to see the answer

Q: Solve the following equation. log5 x = -1

A: Click to see the answer

Q: Solve the following equation: log3(3x) = log3 3 + log3(4x − 1).

A: To solve the below equation

Q: Solve the logarithmic equation. log7 x = 3 II

A: For this problem, we can find x easily by using formula.

Q: solve the following equation: x = log5(1/625)

A: Click to see the answer

Q: Solve the logarithmic equation. ln e^(x+2) = 3

A: To solve the given logarithmic equation, ln e^(x+2) = 3

Q: Solve the following equation: log 7 ( x + 1 ) + log 7 ( x - 5 ) = 1

A: (1) According to the question, we have to solve the expression log7x+1+log7x-5=1. As the given…

Q: Solve the following logarithms for x. 12) log5 225 = 2x-6

A: given :

Q: Solve the following equation: log7(3x) = log7 3 + log7(6x – 1). X =

A: Answer and explanation is given below

Q: Find the solution of the equation, correct to two decimal places. log2(x+2) + log2(x−1)= 2

A: We gonna use log properties to sole this problem log m + log n = log mn loga x = y => x = ay

Q: The value of log; v8 is 2

A: Click to see the answer

Q: Solve the logarithmic equation. log x+ log (x- 9) = 1

A: Use log property

Q: Solve the following: log, (x-2) + log, (x ) = 1

A: Click to see the answer

Q: Solve the following logarithmic equation. Use a calculator where appropriate. log x+ log (x + 3) = 1…

A: The given equation is log x+log(x+3)=1. Use product rule of logarithmic log x+log y=log(xy). Use…

Q: Solve the logarithmic equation: log , (10 – 2x) – log , (x + 3) = 1.

A: Click to see the answer

Q: Solve the logarithmic equation for x. log,(x + 3) - log,(x-3) - 2

A: Click to see the answer

Q: Solve the equation accurate to three decimal places. log7 x3 = 1.9

A: We have given that log7 x3 = 1.9 First, we have to take the common base Take base as 7

Q: Solve the logarithmic equation for the unknown x. 12 log5(5x + 7) = 6 %3D

A: Given : 12log55x + 7 = 6

Q: Solve the given logarithm equation x=log4 3/16

A: Click to see the answer

Q: Express the following logarithms in terms of ln 2 and ln 3. ln 3√9

A: To express: ln 3√9 in terms of ln 2 and ln 3.

Q: Solve the following logarithm problem for the positive solution for x. 1 log, = -2 %3D 49

A: x=?

Q: Solve the following logarithm problem for the positive solution for x. 1 logr 9. 23

A: Logarithmic properties.

Q: Solve the logarithmic equation. log, (6x + 4) log, (2a – 12) O x = 4 O No Solution O x = 0 O x = -4

A: log4(6x+4)= log4(2x-12) log4(6x+4)-log4(2x-12)=0 (6x+4)(2x-12)=40=1 (6x+4)=(2x-12) 6x-2x=-4-12…

Q: Express the following logarithms in terms of ln 2 and ln 3. ln 0.75

A: To express ln0.75 in terms of ln2 and ln3

Q: Solve for x the equation log [ log (2 + log2(x + 1)) ] = 0

A: Given,

Q: Rewrite as a logarithmic equation. Ey = 5

A: Click to see the answer

*arrow_forward*

*arrow_forward*

*arrow_forward*

*arrow_back_ios*

*arrow_forward_ios*